Virtual learning object for the interactive teaching of climate culture in the area of Natural Sciences - Heredia Silva, Jamil Rubén; Heredia Rengifo, Marco Gerardo (SATHIRI, 2025)
The virtual learning object was created as an educational tool designed to foster learning. Although teachers employed various strategies and activities to develop key competencies related to climate culture, the use of digital resources and tools in teaching climate change was limited. For this reason, the study focused on proposing a virtual learning object to teach climate culture in the field of natural sciences, aimed at third-level students of the Instituto Superior Tecnológico Vicente León from Latacunga. The methodology used was mixed, descriptive, and non-experimental, involving 75 students and 8 teachers. Surveys and pretest and posttest evaluations were conducted to collect data. Canva was chosen for designing the virtual object, through five interactive units on climate culture structured, titled Learn About Climate Change, considering aspects of functionality, technology and interactivity. The results showed that students were able to identify various topics related to climate change, they reached an average score of 6,78/10 in the initial evaluation and improved to an average of 7,69/10 in the posttest evaluation. It was demonstrated that the virtual learning object facilitated the acquisition of knowledge dynamically and specifically, contributing to the differentiation of concepts related to climate change and the development of specific skills in the context of sustainable development.
Keywords: learning; climate change; sustainable development; interactive teaching; digital tools